PENGARUH PUPUK ORGANIK DAN PUPUK NPK 16:16:16 TERHADAP PRODUKSI TANAMANLABU MADU (Cucurbita moschata) - Wahyu Nugroho; Zulkifli; Silvia Sutriana (UIR Press, 2025)
The purpose of the study was to determine the interaction and primary effect of organic fertilizer and NPK 16:16:16 on the production of honey pumpkins. This study used a factorial completely randomized design consisting of two factors. The first factor was organic fertilizer with goat manure, guano, and vermicompost, while the second factor was NPK fertilizer 16:16:16, consisting of four levels, namely: 0, 15, 30, and 45 g/plant. Parameters observed were age of flowering, percentage of flowers to fruit, age of harvest, number of fruits per plant, weight of fruit per fruit, and weight of fruit per plant. The observation data were statistically analyzed, and a further BNJ test was conducted at the 5% level. The results showed that the interaction between organic fertilizer and NPK 16:16:16 had a significant effect on flowering age, harvest age, number of fruits per plant, fruit weight per fruit, and fruit weight per plant. The best treatment was organic vermicompost fertilizer and NPK 16:16:16 at 40 g/plant. The main effect of various organic fertilizers was significant for all parameters; the best treatment was vermicompost. The main effect of NPK 16:16:16 was significant on all parameters; the best treatment dose was 40 g/plant.